EVIDENCE FOR PAST KNOT MERGERS IN THE HH34 JET - A. C. Raga (Revista Mexicana de Astronomía y Astrofísica, 2013)
Within ≈30" from the outflow source, the HH34 jet has a chain of well aligned knots. The positions and proper motions of these knots can be used to determine dynamical timescales, and estimates of the ejection period (by taking differences between the dynamical timescales of the successive knots). Through this exercise, we find that larger estimated ejection periods are found for the knots further away from the outflow source (i.e., for the knots with larger dynamical timescales). We interpret this result in terms of a model in which the knots have a low amplitude (≈15–20%) random ejection velocity variability and a well defined period of ≈16 yr, leading to a few knot-merging events.